2021
DOI: 10.3390/antiox10081213
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidants in the Mediterranean Diet

Abstract: Epidemiological studies performed during the second half of the previous century have correlated the diet that prevailed in the north shores of the Mediterranean basin with beneficial health effects, including reduced mortality risk and lower incidences of cardiovascular diseases [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The beneficial health effects of the Mediterranean diet have been often assigned to antioxidants. 33 A recent study also indicated that omega-3 PUFAs intake had antioxidative effects. 12 Furthermore, it has been assumed that dietary antioxidants protect cells and tissues from oxidation and prevent or delay the development of several diseases.…”
Section: Discussionmentioning
confidence: 98%
“…The beneficial health effects of the Mediterranean diet have been often assigned to antioxidants. 33 A recent study also indicated that omega-3 PUFAs intake had antioxidative effects. 12 Furthermore, it has been assumed that dietary antioxidants protect cells and tissues from oxidation and prevent or delay the development of several diseases.…”
Section: Discussionmentioning
confidence: 98%
“…The Mediterranean diet supplies a plethora of vitamins (e.g., β-carotene, vitamin C, vitamin E), minerals, and polyphenols, with antioxidant, anti-inflammatory, and pro-autophagic properties [ 67 , 70 , 71 , 72 ]. For instance, the PREvencion con DIeta MEDiterranea (PREDIMED) study found a decrease in inflammatory biomarkers, such as interleukin 6, C-reactive protein, and leukocyte adhesion molecules, in participants with higher Mediterranean diet adherence [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a wealth of published data for identifying and quantitatively determining phenolic constituents in Thymus plant extracts [ 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 ]. They have been widely investigated for their biological activities in physiological systems, e.g., antioxidant, anti-aging, anticarcinogenic, pro-apoptosis, anti-inflammation, and anti-atherosclerosis.…”
Section: Thymus Algeriensis Boiss and Reutmentioning
confidence: 99%